2016
DOI: 10.1177/0734016816635249
|View full text |Cite
|
Sign up to set email alerts
|

Who Seeks Counseling for Intimate Partner Violence? The Role of Emotional Distress

Abstract: Intimate partner violence (IPV) is a pervasive problem in the United States affecting every demographic group. Victims of IPV suffer a wide range of negative health issues including depression, anxiety, and loss of self-esteem. However, little is known about help-seeking behaviors among IPV victims. This study utilized a university sample to explore who seeks counseling for exposure to threatening IPV. Results revealed that older students and females were more likely to seek counseling than younger students an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Previous studies on informal help-seeking among IPV survivors who had ever had suicide ideations are limited. However, robust literature demonstrates that IPV survivors who seek formal help to stop the violence have higher levels of mental distress (Golding, 1999; Posick et al, 2016). Importantly, we also found that having ever thought of suicide increased the likelihood of receiving an unsupportive response, namely blame.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on informal help-seeking among IPV survivors who had ever had suicide ideations are limited. However, robust literature demonstrates that IPV survivors who seek formal help to stop the violence have higher levels of mental distress (Golding, 1999; Posick et al, 2016). Importantly, we also found that having ever thought of suicide increased the likelihood of receiving an unsupportive response, namely blame.…”
Section: Discussionmentioning
confidence: 99%